Mandibular Incisor Extraction Treatment of a Class I Malocclusion with Bolton Discrepancy: A Case Report - Bayram, Mehmet; Özer, Mete (European Journal of Dentistry, 2007)
Many approaches for crowded mandibular anterior teeth are currently employed: distal movement of posterior teeth, lateral movement of canines, labial movement of incisors, interproximal enamel reduction, removal of premolars, removal of one or two incisors, and various combinations of the above. Selecting the best treatment is often difficult, and all guidelines do not apply to every case. Treatment by extraction of one single mandibular incisor is not popular in the orthodontic profession despite the apparent advantages of the extraction in the region of crowding. A case report is presented one mandibular incisor extraction treatment of a 16 year-old female with a Class I malocclusion that shows a significant mandibular arch length deficiency and mandibular tooth-size excess. In this case, the degree of mandibular anterior dental crowding, existing mandibular tooth-size excess, and the dental midline discrepancy were indicated the extraction of one mandibular incisor. (Eur J Dent 2007;1:54-59)
Keywords: Mandibular incisor extraction; Bolton discrepancy